A synbiotic combination of mixed probiotics and oligofructose restores intestinal microbiota disturbance in DSS-induced colitis in mice - Ma, Weiwei; Lian, Lian; Guo, Lidong; Wu, Yanan; Huang, Lili (Frontiers in Microbiology, 2025)
Both probiotics and prebiotics can regulate gut microbiota and produce metabolites that are beneficial to the host, showing potential therapeutic prospects for ulcerative colitis (UC). This study aimed to investigate the therapeutic effects and mechanisms of low-, medium-, and high-dose probiotic mixtures (Bifidobacterium animalis subsp. lactis XLTG11: Lactobacillus paracasei Glory LP16: Lactiplantibacillus plantarum CCFM8661) combined with oligofructose (FOS) on DSS-induced colitis mice. Male BALB/c mice were induced with 2.5% DSS for colitis and then treated with low-, medium-, and high-dose mixed probiotics and oligofructose synbiotics (6 × 106 CFU probiotics + 1.5 mg FOS synbiotics/day, 6 × 107 CFU probiotics + 1.5 mg FOS synbiotics/day, and 6 × 108 CFU probiotics + 1.5 mg FOS synbiotics/day) for 1 week. Colonic inflammation was evaluated by body weight, diarrhea index, immune organ index and colon length; the protective effect of synbiotics on the intestinal barrier was evaluated by HE staining, ELISA and RT-qPCR to detect the degree of intestinal tissue damage, inflammatory cytokines, intestinal permeability and tight junction proteins. In addition, the intestinal microbiota and short-chain fatty acids (SCFAs) were estimated by metagenomics and LC-MS, respectively, to analyze the mechanism of action of synbiotics in alleviating colitis. The results showed that the combination of mixed probiotics and oligofructose could significantly alleviate the symptoms of colitis in mice, improve the weight loss symptoms of DSS mice, reduce the diarrhea index, restore the colon length, reduce tissue pathological damage, and improve the integrity of the intestinal barrier. In addition, through metagenomic data analysis, mixed probiotics combined with oligofructose can enhance the diversity and richness of gut microbiota, increase the abundance of beneficial bacteria Bifidobacterium and Lactobacillus, promote the production of SCFAs, and enhance intestinal barrier function. It is worth noting that the therapeutic effect of synbiotics depends on the dose of mixed probiotics. This study explored the alleviating effect of synbiotics containing mixed probiotics and oligofructose at different doses on UC, and provided a theoretical basis for guiding the development and use of synbiotic preparations that regulate the homeostasis of gut microbiota.